Compound Discovery and Structure-Activity Relationship Study of Neoantimycins Against Drug-Resistant Cancer Cells - Lin, Xiao; Zhou, Yongjun; Liu, Liyun; Zhu, Hongrui; Chen, Yeping; Wang, Shuping; Sun, Fan; Chai, Ling; Liu, Buming; Xu, Shihai; Lin, Hou-Wen (Frontiers in Chemistry, 2019)
Four neoantimycins H-K (1-4) with C1-keto, including the new ones (1-2), were isolated from the culture of Streptomyces conglobatus RJ8. After enzymatically converting into their respective reduced type derivatives (5-8) in vitro, the absolute structures of 1-8 were established/reconfirmed by analyzing hydrolyzed components. The obtained NATs (4, 7 and 8) exhibited excellent cytotoxicity against drug-resistant colon and gastric cancer cells but low toxicity in the noncancerous cell. Further SAR investigation suggested that C1-hydroxyl, C9-isobutyl, and N-formyl contribute to the antiproliferation remarkably.